Giant posterior fossa arachnoid cyst causing tonsillar herniation and cervical syringomyelia - Joshi, Vijay P. (Medknow Publications & Media Pvt Ltd, 2013)
Acquired cerebellar tonsillar herniation and syringomyelia associated with posterior fossa mass lesions is an exception rather than the rule. In the present article, we describe the neuroimaging findings in a case of 28-year-old female patient presented with a history of paraesthesia involving right upper limb of 8-month duration. Magnetic resonance imaging showed a giant retrocerebellar arachnoid causing tonsillar herniation with cervical syringomyelia. The findings in the present case supports that the one of the primary mechanism for the development of syringomyelia may be the obstruction to the flow of cerebrospinal fluid causing alterations in the passage of extracellular fluid in the spinal cord and leading to syringomyelia.